Pengaruh Strategi PQ4R (Preview, Question, Read, Reflect, Recite, Review) Terhadap Minat Belajar dan Retensi (Daya Ingatan) Peserta Didik pada Mata Pelajaran Sejarah Kebudayaan Islam di MTsS Harapan Bangsa - Ilma Hasanah; Anton Widyanto; Zulfatmi Zulfatmi (Tadabbur: Jurnal Peradaban Islam, 2023)
This This study aimed to investigate the effect of preview, question, read, reflect, recite, and review (PQ4R) strategy on students’ learning interest and retention (memory). The study used an experimental method, utilizing a quasi-experimental design with a pretest-posttest non-equivalent control group model. This study took place at MTsS (private Islamic junior high school) Harapan Bangsa in West Aceh District, Aceh, Indonesia in the even semester of the 2022/2023 Academic Year. The sample of the study consisted of 40 students in the experimental group and 40 students in the control group. The parameters measured in this study were learning interest and retention. Data on learning interest were analyzed by using the ANACOVA parametric statistical test while data on retention were analyzed by using the percentage formula. The results of the study showed that the learning interest of students who used the PQ4R learning strategy was higher than those who studied conventionally, with a score of 83 for the experimental class and 66 for the control class. This could be seen from the results of 30.80 > 3.97 (Fcount > Ftable), indicating the hypothesis Ha was accepted. Further, retention (memory) of students using the PQ4R learning strategy also differed, namely 89 for the control class and 95 for the experimental class. The study concludes that the application of the PQ4R strategy has an effect on the students’ learning interest and retention (memory) in the subject of Islamic Cultural History at MTsS Harapan Bangsa.